INOVASI FUDGY BROWNIES DENGAN SUBTITUSI TEPUNG SUKUN DAN PENAMBAHAN EKSTRAK DAUN JELATANG (Urtica dioica) - Rilla Puspa Sari; Ita Fatkhur Romadhoni; Qorry' Aina; Mafisa Restami (JURNAL ILMIAH PENELITIAN MAHASISWA, 2026)
This research is driven by the diversification of local food through the innovation of fudgy brownies utilizing breadfruit flour substitution (10%, 20%, 30%) and nettle leaf (Urtica dioica) extract addition (2%, 4%). The study aimed to analyze the sensory quality characteristics, determine the optimal formula, and evaluate the nutritional content of the product. A quantitative experimental method was applied, involving 30 semi-trained panelists for the sensory characteristics, followed by data analysis using Two-Way ANOVA. Statistical results indicated that treatment variations significantly affected aroma (p=0.013) and texture (p=0.046) characteristics, while showing no significant effect on color, taste, and overall preference. The P1S1 formula (10% breadfruit flour and 2% nettle leaf extract) was selected as the best and most accepted product, scoring 3.97 for both taste and overall appreciation. Based on laboratory proximate analysis, every 100 grams of this optimum formula contains a total energy of 479.73 kcal, 53.915% carbohydrates, 26.57% total fat, 6.235% protein, 11.4% moisture, and 1.88% ash content. This innovative product holds great potential to be developed as a commercial functional snack alternative that is nutrient-dense and based on local commodities.